The devil is in the mesoscale: Mechanical and behavioural heterogeneity in collective cell movement. (September 2019) - Blanchard, Guy B.; Fletcher, Alexander G.; Schumacher, Linus J.
Highlights: Tissue morphogenesis requires tightly coordinated behaviours such as collective cell movements. Heterogeneity in individual cell behaviours can result in complex and counter-intuitive tissue-level behaviour. Multicellular 'mesoscale' structures can be a signature of such heterogeneity. Appropriate methods are needed to detect and quantify mesoscale features. Computational models can help probe the formation and role of mesoscale structures. Abstract: Heterogeneity within cell populations can be an important aspect affecting their collective movement and tissue-mechanical properties, determining for example their effective viscoelasticity. Differences in cell-level properties and behaviour within a group of moving cells can give rise to unexpected and non-intuitive behaviours at the tissue level. Such emergent phenomena often manifest themselves through spatiotemporal patterns at an intermediate 'mesoscale' between cell and tissue scales, typically involving tens of cells. Focussing on the development of embryonic animal tissues, we review recent evidence for the importance of heterogeneity at the mesoscale for collective cell migration and convergence and extension movements. We further discuss approaches to incorporate heterogeneity into computational models to complement experimental investigations.